2015
DOI: 10.1186/s12984-015-0040-6
|View full text |Cite
|
Sign up to set email alerts
|

Frailty assessment based on trunk kinematic parameters during walking

Abstract: BackgroundPhysical frailty has become the center of attention of basic, clinical and demographic research due to its incidence level and gravity of adverse outcomes with age. Frailty syndrome is estimated to affect 20 % of the population older than 75 years. Thus, one of the greatest current challenges in this field is to identify parameters that can discriminate between vulnerable and robust subjects. Gait analysis has been widely used to predict frailty. The aim of the present study was to investigate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 38 publications
4
56
0
1
Order By: Relevance
“…The measured kinematic spatiotemporal parameters, which have been associated with gait disorders [30,31,32,33,34,35] in frail adults [36,37], were: step and stride regularity [30], gait symmetry [37], gait variability, the signal root mean square (RMS) value and the approximate entropy (ApEn) [38,39]. The frequency parameters analyzed were the harmonic ratio (HR) and the total harmonic distortion (THD) [37].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measured kinematic spatiotemporal parameters, which have been associated with gait disorders [30,31,32,33,34,35] in frail adults [36,37], were: step and stride regularity [30], gait symmetry [37], gait variability, the signal root mean square (RMS) value and the approximate entropy (ApEn) [38,39]. The frequency parameters analyzed were the harmonic ratio (HR) and the total harmonic distortion (THD) [37].…”
Section: Methodsmentioning
confidence: 99%
“…The frequency parameters analyzed were the harmonic ratio (HR) and the total harmonic distortion (THD) [37]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests have been extensively used to assess gait ability (Freiberger et al 2012;Cadore et al 2013;CasasHerrero et al 2013;Martínez-Ramírez et al 2015). The starting and ending points were marked on the floor with tape lines and included a total distance of 7 m. The first and last meters, i.e., the warm-up and deceleration phases, respectively, were not included in the calculations for the gait assessments.…”
Section: Participantsmentioning
confidence: 99%
“…Specifically, stride time variability under fast gait conditions was most consistently associated with frailty . Martinez‐Ramirez et al found that gait speed, trunk acceleration RMS and harmonic distortion were significantly different between different frailty groups . Furthermore, spatial–temporal gait characteristics, such as stride time, stride length and double support, could distinguish different frailty statuses .…”
Section: Introductionmentioning
confidence: 99%